Türkçe Kısa Metinlerde Yazar Tanıma Yönteminin Sınanması ve Geliştirilmesi. - TANRIVERE, Utku (Journal of Faculty of Letters / Edebiyat Fakultesi Dergisi, 2020)
Author identification is probably one of the most important applications of forensic linguistics. Considering scientific literature in Turkish language, related studies have been carried out relatively recently and very short texts have not been used in these studies (Amasyalı & Diri, 2006; Taş & Görür, 2007; Doğan & Diri, 2010). However, texts involving only a few words may also be a subject of study in terms of forensic linguistics. In the past, as a result of a study on published texts (tweets) on a micro-blog site "Twitter", a method in the scientific literature in the Turkish language had been proposed (Tanrıvere, 2018). In the present study, however, that very method has been tested with a new corpus consisting of tweets again, and the markers within the method were developed by increasing the number and making elaborations qualitatively. This method has brought about successful results by comparing texts with known and unknown authors. In the implementation process, there have been some distinctive but unpredicted markers. These were also given in detail and proposed to be added to the relevant marker group within the method. The results of the study have shown in general author identification is possible even in very short texts and the method may also be used in forensic contexts.